Keputusan IOC (International Olympic Committee)Memilih London sebagai Tuan RumahOlimpiade 2012 Decision of IOC (International Olympic Committee) Choose London as Olympic’s Host 2012 - Muhammad Wahyu Ghifari (HI 16 UMY 181, 2016)
*181 Olympics is an event of multi-sport event held every four years. In the four yearly also chosen to host the Olympic host. As well as to host the 2012 Olympic Games the IOC (International Olympic Committee) selects several candidates to host. The prospective hosts are Havana, Leipzig, Istanbul, Rio de Janerio, Moscow, Madrid, New York, London and Paris. Of the nine candidates to host the IOC carry out assessment of several aspects: Accommodation, Environmental conditions and impact, Experience from past sports events, Finance, General Infrastructure, Government support, legal issues, public opinion, the Olympic Village (s), Overall Project and legacy, Safety and security, Sports venues, Transport concept. The results of the assessment resulted in Paris with a score of 8,5, followed by Madrid (8,3), London (7,6), NewYork (7,5), Moscow (6,5), Leipzig (6,0), Rio de Janerio (5,1), Istanbul (4,8) and Havana (3,7). Five candidates to host the highest scoring will do next selection stage. The next selection stage held on to the 117th IOC Session in Singapore. System at this stage through voting. Voting systems conducted over four rounds with each round the candidate who got the lowest voting must be eliminated. At the roundabout, Moscow should be eliminated first followed by New York in the second round, the third round in Madrid and Paris in the last round. From the result of voting Olympic’s host 2012 was London.